Diagnostic Value of Neutrophil to Lymphocyte Ratio and Mean Platelet Volume on Early Onset Neonatal Sepsis on Term Neonate - Karabulut, Birol; Alatas, Silem Ozdem (Journal of Pediatric Intensive Care, 2020)
By setting out from increased neutrophil count, decreased lymphocyte count, and increased mean platelet volume (MPV), which is a result of the effect of inflammation on blood cells, we aimed to investigate whether neutrophil to lymphocyte ratio (NLP) and MPV can be used as an auxiliary parameter for the diagnosis of early-onset neonatal sepsis (EOS). This study was conducted by analyzing term neonates with EOS and physiological jaundice who were admitted to the neonatal intensive care unit of Izmir Katip Celebi University Ataturk Training and Research Hospital. A total of 63 neonate files were examined to include 30 term neonates with EOS, and 77 neonate files were examined to include 30 term neonates with physiological jaundice as a control group. NLR had an area under the curve (AUC) of 0.891 for prediction of EOS. At a cut-off level of 1.42, NLR had a likelihood ratio (LR) of 5.5, sensitivity of 88%, a specificity of 84%, a positive predictive value (PPV) of 84.6%, and a negative predictive value (NPV) of 87.5%. MPV had an AUC of 0.666 for the prediction of EOS and at a cut-off level of 9.3 fL, MPV had an LR of 1.23, sensitivity of 84%, a specificity of 32%, a PPV of 55.2%, and an NPV of 66.6%. In conclusion, this study provides evidence that NLR and MPV can be used in addition to conventional parameters in the diagnosis of EOS.
Keywords: neutrophil; lymphocyte; mean platelet volume; sepsis